ENHANCED SENSITIVITY OF SURFACE PLASMON RESONANCE SENSOR BASED ON COMBINATION OF Au/PEDOT:PSS NANOLAYERS - Nguyen Van Sau; Ma Thai Hoa; Nguyen Xuan Thi Diem Trinh; Nguyen Tan Tai (Tạp chí Khoa học Đại học Đà Lạt)
This paper simulates an optical sensor utilizing a prism based on surface plasmon resonance (SPR). The simulations combine a layer of Au and an additional layer of different materials: aluminum arsenide (AlAs), poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), zinc oxide (ZnO), and polydimethylsiloxane (PDMS) for SPR excitation. The simulations show that a sensor based on a combination of Au/PEDOT:PSS layers with thicknesses of 40 nm and 5 nm, respectively, offers a sensor sensitivity of 186.07°/RIU, which is 1.2 times better than that of a sensor using only a thin Au layer. The enhancement in sensor sensitivity offers advantages for early detection of small concentrations of bacteria in biomedical and chemical applications.